METHODOLOGICAL FUNDAMENTALS OF PRACTICAL TRAINING OF GUARDS FOR PROFESSIONAL ACTIVITIES IN EXTREME SITUATIONS (Innovative professional education, 2024)
This article is devoted to the analysis of methodical approaches to the practical training of security guards for effectiveprofessional activity in extreme situations. Various aspects of training are covered, including marksmanship, combat and communication skills, as well as psychological training and first aid. The article highlights key aspects of training that help security guards respond effectively to emergency situations and keep their clients safe.
Keywords: methodological bases of professional training, bodyguards, extreme situations, shooting, self-defense, communication, psychological training, tactical medicine, extremology